Influence Timeliness and Price Against Loyalty Customer With Satisfaction Customer As Intervening Variables at PT.XYZ - Pahrudin, Cecep; Zaini, Mohamad; Fadillah, Hirosi; Iyumiwa, Salsabila (Dinasti International Journal of Management Science, 2024)
This article is results from purposeful research For analyze about accuracy time and price delivery goods from company PT XYZ Good in a way Partial nor in a way influential simultaneous to loyalty customer through satisfaction customer as intervening variables. Method or tool analysis in study This use SmartPLS software 4 ie For test hypothesis influence variable independent to variable dependent Good in a way direct nor through variable intervening to loyalty customer. Test result state that accuracy time influential to satisfaction customers, price influential to satisfaction customer, satisfaction customer influential to loyalty customer, accuracy time No influential to loyalty customer ( rejected ), price influential to loyalty customer, accuracy time through satisfaction customer influential to loyalty customers, and prices through satisfaction customer influential to loyalty customer. From the results study This can concluded that there is 1 hypothesis that is not accepted or rejected that is accuracy time to loyalty customer. However with put satisfaction customer as variable intervening own positive implications and value important can accept hypothesis.